ANTROPOLOGIENS SKIFTENDE OBJEKT: Om politisk og kulturel autonomi. Eksempler fra Sydamerika - Fock, Niels (Tidsskriftet Antropologi, 1996)
anthropology: on political and cultural autonomy among Indigenous peoples in South America Considering the historical and theoretical notions of the object of study during the last flfty years of Danish anthropology it is sketched how developments in world politics, in local indigenous societies and in the discipline of anthropology have forced anthropologists to take new stands. During the fnst twenty years the academic establishment was at the fore, while world politics was a very dominant factor for the next two decades. Apparently indigenous peoples have in the last decade tumed increasingly explicit about the advisory role of anthropology, not least in relation to human rights. Tove Søvndahl Petersen: An Indigenous people with home rule The establishment of the Greenland Home Rule Government in 1979 has meant political influence for the Greenlanders, after more than 200 years of colonial rule. Indigenous peoples today look towards the Greenland Home Rule as an ideal. Greenlanders’ own acceptance of an identity as indigenous came, however, quite late, and the Greenland identity has throughout history been marked by the relatively unviolent Danish colonisation. Home Rule means new challenges to Greenland identity, at the same time as it provides freedom to form future strategies for the Greenlanders in persuasive ways.